Optimization of Propeller Tunnel Design for the Polbeng II Ship - Jupri, Jupri; B, Siswandi; Afriantoni, Afriantoni; Efrizal, Efrizal; Hanif, Fadzi; Hadri, Muhammad Arika (ABEC Indonesia, 2024)
The Polbeng II ship is one of the crew vessels owned by Bengkalis State Polytechnic. This ship plays a vitalrole in supporting various research and exploration activities in the waters of Bengkalis. To enhance the ship'sperformance in terms of speed, the addition of a propeller tunnel component has significant potential to improve thevessel's speed and efficiency. The tunnel is designed based on the propeller diameter (D) used by the Polbeng II ship, andthis study compares several design model variations of 20%D, 30%D, 40%D, and 50%D in relation to the distance fromthe rudder. The objective is to achieve the highest flow pressure value among the four design model variations using CFDevaluation based on an input fluid flow velocity of 1 m/s. The evaluation results indicate that the model with 40%Dyields the highest pressure value of 103.73 pascals, along with a flow velocity of 2.018 m/s.